O dispositivo apoio matricial em saúde mental no Núcleo de Apoio à Saúde da Família: uma clínica da transicionalidade? - Bei, Alice Wilmers (2012)
This research concerns the study of mental health wide-spectrum clinic in primary care, put in practice by monitoring the Matrix Support activities of a Center for Support to Family Health (NASF) team in São Paulo. The aim was to reflect on the type of clinic interaction produced between the NASF team and a family health team (ESF), focusing on the "imaginary of madness", the medication issue and the possibility of creating new modes of Subjectivation. In order to accomplish this the study used a case under construction by the two teams, analyzing how NASF's support facilitates, or not, the process of producing an extended clinic, transforming the traditional clinic. In this sense, the study used the concept of transitionality presented by Winnicott in order to reflect on the creative experiences and those of singularization, and to discuss the creation of new modes of Subjectivation in the clinic generated between the teams concerned. In this study, NASF has been recognized as important by the ESF, so it was offered help and support when dealing with complex cases, beyond psychiatric intervention and understanding of mental disorders; support was still considered in face of a chaotic reality, which itself generates illnesses. However, in this context, the majority of professionals has demonstrated difficulty in creating new clinical interventions, which might go beyond those already established. In order to better allow for creative processes and experiences of transitionality emerged out of the clinic, the need was recognized for more support to professionals, especially those of NASF, who offer matrix support, but do not receive it